Role of bioconvection, porous medium, and activation energy on the dynamic of Sisko nanofluid: the case of an enlarging cylinder - Habib, Danial (2022)
The current problem is attributed to various features of Sisko nanofluids flow over-stretching cylinder along bioconvection of motile microorganisms in the presence of activation energy and non-Fourier thermal diffusion. The appropriate methodology is adopted to transform the governing boundary layer equations of fluid flow into the dimensionless nonlinear ODEs. The transformed coupled nonlinear differential equations are resolved numerically with MATLAB software with Bvp4c (Lobatto-IIIa) solver. The effect of dissimilar parameters viz., the Sisko material parameter, porosity parameter, bioconvection Lewis number, thermophoresis parameter, and bioconvection parameter on the velocity, temperature, concentration, and micro-organisms distribution are presented in numeric and graphics modes. The porous drag force of the Darcian linear system is used to evaluate the porosity parameter. It is also noticed that the numerical values of the porosity parameter reduced the velocity while it is enhancing the temperature. This research of wall cooling and heating bears is indispensable applications in solar porous water absorber systems, chemical engineering, space technology, metallurgy, substantial processing, and so forth.